2023
DOI: 10.1101/2023.11.17.567594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota-dependent increase in phenylacetic acid induces endothelial cell senescence during aging

Seyed Soheil Saeedi Saravi,
Benoit Pugin,
Florentin Constancias
et al.

Abstract: Endothelial cell (EC) senescence plays a crucial role in the development of cardiovascular diseases in aging population. Gut microbiota alterations are emerging as significant factors present in cellular senescence associated with aging. However, little is known about how aging-related changes in gut microbiota are causally implicated in EC senescence. Here we show that gut microbiota-dependent phenylacetic acid (PAA) and its derivative, phenylacetylglutamine (PAGln), are elevated in a human aging cohort (Twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 60 publications
4
9
0
Order By: Relevance
“…Excessive H 2 O 2 and other ROS within SECs disrupt the phosphorylation responses of these protein kinases. This observation aligns with our recent studies indicating that CaMKII phosphorylation declined in SECs, in which mitochondrial ROS induces oxidative stress [22]. The diminished CaMKII phosphorylation due to oxidative stress can impair its downstream signaling cascades, contributing to endothelial dysfunction [55].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Excessive H 2 O 2 and other ROS within SECs disrupt the phosphorylation responses of these protein kinases. This observation aligns with our recent studies indicating that CaMKII phosphorylation declined in SECs, in which mitochondrial ROS induces oxidative stress [22]. The diminished CaMKII phosphorylation due to oxidative stress can impair its downstream signaling cascades, contributing to endothelial dysfunction [55].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, oxidized HDAC4 has been shown to interact more easily with protein kinases of the CaMKII family. Consistently, our prior investigation demonstrated that gut-derived phenylacetic acid, by NOX4-mediated H 2 O 2 generation, both oxidizes and phosphorylates (through CaMKII stimulation) HDAC4, facilitating its cytosolic accumulation in PECs [22]. We next observed that HDAC4 nuclear export facilitates de-repression of Mef2A in PECs.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations